2018
DOI: 10.1002/iub.1747
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐223 inhibits lipopolysaccharide‐induced inflammatory response by directly targeting Irak1 in the nucleus pulposus cells of intervertebral disc

Abstract: This study was aimed to research the effect of miR-223 on the inflammatory responses induced by lipopolysaccharide (LPS) in nucleus pulposus (NP) cells of rat intervertebral disc. Isolated rat NP cells were induced by LPS. Reverse transcriptase quantitative real-time polymerase chain reaction was used to detect gene expression. To detect protein expression, Western blot and enzyme-linked immunosorbent assay experiments were applied. The putative targeting relationship between miR-223 and Irak1 was determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
(40 reference statements)
2
27
0
Order By: Relevance
“…MiR - 223 was shown to be downregulated in the lungs of rats exposed to CS [80]. It has been shown that the overexpression of miR - 223 suppresses LPS-induced NF - κB signaling by targeting IL - 1 receptor-associated kinase 1 [184]. Recent data have revealed the upregulation of miR - 223 as a novel biomarker in subsets of patients with inflammatory bowel disease [185].…”
Section: Epigenetics and Inflammationmentioning
confidence: 99%
“…MiR - 223 was shown to be downregulated in the lungs of rats exposed to CS [80]. It has been shown that the overexpression of miR - 223 suppresses LPS-induced NF - κB signaling by targeting IL - 1 receptor-associated kinase 1 [184]. Recent data have revealed the upregulation of miR - 223 as a novel biomarker in subsets of patients with inflammatory bowel disease [185].…”
Section: Epigenetics and Inflammationmentioning
confidence: 99%
“…The previously reported close association between cul4B and inflammation suggested that there might an anti-inflammatory effect exerted by Syra in the survival of damaged nP cells. Indeed, the onset of inflammation induced by LPS in NP cells and the anti-inflammatory effect of SyrA has been confirmed in many prior reports (37)(38)(39)(40)(41). deGs in the 'apoptosis-multiple species' pathway include aPaF1, Birc3 and Bcl2.…”
Section: Lps-stimulated Groups Syra-reversed Groups -----------------mentioning
confidence: 61%
“…notably, the level of cullin 4B (cul4B) was found to be significantly upregulated in IDD samples compared with the controls, and this was positively correlated with the severity of idd (36). in addition, the expression of cul4B was enhanced after treatment with the inflammatory factors interleukin (il)-6 and tumour necrosis factor (TnF)-α, and reversed by il-6 and TnF-α inhibitors in primary nP cells (37). The previously reported close association between cul4B and inflammation suggested that there might an anti-inflammatory effect exerted by Syra in the survival of damaged nP cells.…”
Section: Lps-stimulated Groups Syra-reversed Groups -----------------mentioning
confidence: 97%
“…However, miR-233 can also target other genes, such as Irak1. 18 Our future studies will investigate the involvement of other targets of miR-233 in CSCC.…”
Section: Discussionmentioning
confidence: 99%